Metode dan Ideologi Penerjemahan Makna Kanyouku Organ Tubuh dalam Cerpen Kappa Karya Akutagawa Ryuunosuke - Andriani, Natalia; Rauh Artana, I Nyoman; Ratna Dian Aryani, Made (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2019)
The research entitled "Translation Method and Ideology of Organ Kanyouku in Akutagawa Ryuunosuke's Short Story “Kappa" is aimed to study the methods and ideologies of translation applied in Akutagawa Ryuunosuke's short story, Kappa. The data source of the study is a short story entitled “Kappa” written by Akutagawa Ryuunosuke. This research was analyzed using the descriptive analysis method. The analysis of the translation method uses the method of translation theory by Newmark (1988), the ideology of translation theory by Venuti (2000) and the translation shift theory by Nida and Taber (1982). The results of this research indicates that in translating 19 kanyouku found in the data source. The translators only use five out of eight translation method proposed, there are two kanyouku use the communication translation method, 11 kanyouku use free translation methods, two kanyouku use the adaptation translation method; one kanyouku uses word for word translation method; and three kanyouku use the literal translation method. Regarding the ideology of translation by Venuti (2000), the results of this study indicates that there are 15 kanyouku that are translated through domestication and four kanyouku are translated through foreignization.